Factors Affecting Market Share of Iranian Hand-woven Carpet in Singapore - Agheli, Lotfali; Salmani, Unes; Hosseini, Mir Abdullah (International Journal of Economics and Financial Issues, 2017)
The problems created by single product economy have made the promotion of non-oil exports for Iran inevitable. In this context, the empowerment of the Iranian hand-woven carpet rank in target export markets is of considerable importance. Accordingly, using gravity model this paper examines the factors affecting the market share of the Iranian hand-woven carpet in Singapore during 1989-2015. In this regard, a modified gravity model is constructed in terms of characteristics of Singapore market. The estimation results show that decrease in export price of Iranian hand-woven carpet with respect to average carpet prices in Singapore, increase in financial support of Iranian hand-woven carpet exports, increase in real exchange rate, decrease in structural difference between Iran and Singapore economies lead to increase in Iranian market share in Singapore. In addition, increase in Singaporean per capita income with respect to Iran, and increase in employment share of population of Iran with respect to rivals have positive effects on Iranian hand-woven carpet share, while ever-changing exchange rate regimes over 1993-2002, and exchange rate unification policy from 2002 onwards in Iran influence negatively the Iranian hand-woven market share in Singapore. Keywords: Iranian hand-woven carpet, Gravity model, Market share JEL Classifications: F14, F19, F31